PERSEPSI PENTINGNYA KEMAMPUAN KOMUNIKASI : PERBANDINGAN ANTARA AKUNTAN PROFESIONAL DAN MAHASISWA MAGISTER AKUNTANSI - irwansyah, Irwansyah (UNIB Press, 2019)
This research aims to test the communication capabilities and differences ofperception of the importance of communication skills among students with amaster's degree in professional accounting accounting. The study also tested theinfluence of communication ability against the perception of the importance ofcommunication skills. Primary data in this study were obtained from the master ofaccounting students University of bengkulu and professional accountants on theBPKP of bengkulu province by using a survey approach by disseminatingquestionnaires. The questionnaires were distributed to 90 respondents, but only75 questionnaires that can be analyzed or processed. Data analysis in this study isused Independent sample t-test and analysis of simple linear regression.The results showed that: (1) a professional accountant has interpersonalcommunication skills higher than master's degree accounting students, (2) aprofessional accountant has the perception of the importance of bettercommunication skills higher than master's degree accounting students, (3)communication skills has positive effect toward the perception of the importanceof communication skills.